STUDI FITOKIMIA DAN ANALISIS GUGUS FUNGSI ESKTRAK DAUN SIRIH MERAH, DAUN SIRIH BUAH DAN DAUN SIRIH CINA ASAL SORONG PAPUA BARAT DAYA - Mahmud Sulthon Khoiruzaman; Wahyuni Watora (Universitas Pendidikan Muhammadiyah Sorong, 2025)
Indonesia has many plants that have medicinal properties, which are used to cure diseases. Medicinal plants native to Indonesia have quite promising potential, one of which is red betel leaf (Piper crocatum Ruiz) which contains phytochemical compounds including flavonoid compounds. Flavonoid compounds in betel leaves (Peperomia pellucida L.), fruit betel leaves (Piper betle L.) and Chinese betel leaves (Peperomia pellucida L.) herbal plants belonging to the Piperaceae family, have the ability to act as growth antibiotics against bacteria that cause acne, herbal plants included. The functional group (CO) of alcohol, ether, carboxylic acid, ester is of strong intensity with a frequency area of around 1050 - 1300. – 1360 and medium intensity with a frequency area of 3300 – 3500.. Functional group (CC) of strong intensity alkanes with a frequency area ranging between 1340 – 1470 and 2850 – 2970.. Alkene functional group (C= C) intensity varies with the frequency area around between 1610 – 1680..And the functional groups detected are the (C=O) aldehyde group, ketone, alcohol, ether, carboxylic acid, ester with a frequency area ranging between 1690 – 1760.